Internally driven large‐scale changes in the size of Saturn's magnetosphere. Issue 9 (10th September 2015) - Pilkington, N. M.; Achilleos, N.; Arridge, C. S.; Guio, P.; Masters, A.; Ray, L. C.; Sergis, N.; Thomsen, M. F.; Coates, A. J.; Dougherty, M. K.
Abstract Saturn's magnetic field acts as an obstacle to solar wind flow, deflecting plasma around the planet and forming a cavity known as the magnetosphere. The magnetopause defines the boundary between the planetary and solar dominated regimes, and so is strongly influenced by the variable nature of pressure sources both outside and within. Following from Pilkington et al. (2014), crossings of the magnetopause are identified using 7 years of magnetic field and particle data from the Cassini spacecraft and providing unprecedented spatial coverage of the magnetopause boundary. These observations reveal a dynamical interaction where, in addition to the external influence of the solar wind dynamic pressure, internal drivers, and hot plasma dynamics in particular can take almost complete control of the system's dayside shape and size, essentially defying the solar wind conditions. The magnetopause can move by up to 10–15 planetary radii at constant solar wind dynamic pressure, corresponding to relatively "plasma‐loaded" or "plasma‐depleted" states, defined in terms of the internal suprathermal plasma pressure.